COMPARISON OF ACUTE ISCHEMIC STROKE FUNCTIONAL OUTCOME IN SMOKERS AND NONSMOKERS MEASURED BY CANADIAN NEUROLOGICAL SCALE (CNS) AND NIHSS - Putri, Nila Novia; Islam, Mohamad Saiful; Subadi, Imam (Malang Neurology Journal, 2018)
Background. Stroke is the world’s second leading cause of death and main cause of disability. Smoking is a well-known risk factor of stroke. However, the correlation between smoking and stroke outcome is still remains a controversy.Objective. To analyze the differences of functional outcome between smokers and non-smokers in acute ischemic stroke patients.Methods. The design used in this study is retrospective cross-sectional. The functional outcomes of acute ischemic stroke were measured by Canadian Neurologic Scale (CNS) and NIHSS over a period of seven days after the onset of stroke. Differences of CNS and NIHSS were analyzed using Mann-Whitney U test.Results. Median of CNS in smokers and non-smokers were 9.0 and 11.0, respectively. Median of NIHSS in smokers and non-smokers were 4.0 and 2.0, respectively. There were no significant differences in the analysis of CNS score between smokers and non-smokers and NIHSS score analysis between smokers and non-smokers.Conclusion. Smoking is not correlated with the functional outcome in acute ischemic stroke patients measured by CNS and NIHSS.